Isolation, Biotyping And Antibiogram Evaluation Of Brucella Abortus In Cattle And Buffaloes From Punjab (India) (Applied Biological Research, 2013)
The present study was based on the isolation, identification and biochemical  characterization of Brucella species, the causal pathogen of brucellosis, from the  samples taken from cattle and buffaloes in Punjab (India). Out of the 84 samples  of vaginal mucus (35), foetal stomach content (31), foetal membranes (11) and  uterine discharges (7), collected from aborted cattle (29) and buffaloes (55), 9  (10.7%) were positive through isolation. Of these 9 isolates, one isolate was typed  as biotype 2, one as biotype 3 and seven as biotype 1. Prevalence of Brucella  abortus through isolation in buffaloes and cattle was 10.9 and 10.3%,  respectively. Maximum number of B. abortus isolations in cattle (25.9%) and  buffaloes (41.2%) were obtained from the animals in age group of 4-6 years. All  the brucellosis positive animals had history of abortion in 6-9th month of  gestation. Antimicrobial sensitivity revealed that B. abortus was sensitive to  doxycycline, oxytetracyclin, ampicillin, gentamicin, enrofloxacin, streptomycin,  neomycin, chloramphenicol, norfloxacin and kanamycin but resistant to  penicillin, cephalothin, cotrimoxazole and erythromycin.
Keywords: Antimicrobial sensitivity; biotypes; Brucella abortus; brucellosis; buffalo; cattle